Characteristics of Calcium Plasma Parameters by Laser-Induced Breakdown Spectroscopy Technique - Hachim , Hanaa S.; Aadim, Kadhim A. (Iraqi Journal of Science, 2022)
In this work, the effect of laser energy on the properties of a calcium plasma generated by a Q-switched Nd: YAG laser at the fundamental wavelength was studied using spectroscopy. The Boltzmann plot and Stark broadening method were used to measure the main plasma parameters (electron temperature and electron density). The electron temperature ranged ( 0.169 -0.172 ) eV, the electron density ranged ( 2.10 – 2.63 ) for laser energy range of ( 400 – 700) mJ. Other basic plasma properties were also measured, including the Debye length, the number of particles in the Debye sphere, and the plasma frequency. Laser energy affects all plasma parameters, according to our results.